Beer Lover's Mid-Atlantic : Best Breweries, Brewpubs & Beer Bars. - Kolesar, Bryan J. (Beer Lovers Series., 2015)
Beer Lover's Mid-Atlantic features breweries, brewpubs and beer bars geared toward hop heads looking to seek out the best beers--from bitter seasonal IPAs to rich, dark stouts--Pennsylvania, Maryland, New Jersey, and Delaware have to offer. Beer Lover's guides also offer beer receipes for home brewers, regional food recipes that incorporate beer, suggested regional food and beer pairings, and walkable pub crawl itineraries for craft beer-centric destinations.